(untitled) (Bangladesh Medical Journal, 2019)
Here described two cases where mother is the main perpetrators of the event and the victims were their children in the age group of 1 year to 12 years. In 1st case 35 years lady killed her three daughters ages 12, 9, 1 by strangulation then hanged in south surma Sylhet city. In 2nd case A 32 years old married women killed her two sons (ages 5 & 8yrs ) by poisoning and later she died by hanging in Sylhet city . Autopsy examination revealed ligature mark over neck consistent with that of antemortem hanging and ligature marks round the child’s neck were strangulation case also poison found by chemical examination. So it’s time to take awareness within community and take prevention such like notorious incident. Bangladesh Med J. 2017 Sep; 46 (3): 104-106